Anticoagulant activity and toxicity profiles of Melastoma malabathricum linn. leaf extract - Manicam, Caroline (2011)
The increased rates of thrombotic diseases contribute to the high number of morbidity and deaths worldwide each year. For many decades, the use of anticoagulant drugs, namely warfarin, heparin and their derivatives in the prevention and treatment of these maladies remain indisputable. Although these anticoagulant agents are efficacious key players in the clinical practice, they are associated with many well-established drawbacks that limit their usefulness. Hence, there exists an unmet need for equally potent but novel anticoagulant agents with improved safety profiles and ease of administration via the oral route. This study was, thus initiated in view of the current highlights in the medical realm of anticoagulation and based on the preliminary finding in a screening study of Melastoma malabathricum Linn. leaf extract. Melastoma leaves gave the highest extract yield (288.0 ± 1.0 g) when extracted with hot water under reflux, compared to cold water (143.0 ± 5.5 g) and organic solvent (189.0 ± 0.9 g) extraction methods. Hot water extract was also found to possess potent in vitro anticoagulant activities, comparable to conventional drug, heparin. Correspondingly, the Melastoma leaf extract significantly (P < 0.001) prolonged activated partial thromboplastin time (aPTT) (64 - 300 s) in a concentration-dependent manner (l00-1000 ug/ ml), but did not affect both prothrombin time (PT) and thrombin time (TT), suggestive of its effect on the intrinsic pathway of coagulation cascade. There were no inter-gender variations in the trends of anticoagulant activities. The nature of the anticoagulation caused by the extract investigated in immediate and timed-incubation mixing studies, demonstrated that the initially prolonged a PTT of test samples spiked with a range of Melastoma leaf extract was subsequently corrected to normal clotting time (31.0 - 46.6 s) range when test samples were subjected to 50 % normal human plasma. Subsequent analysis of various coagulation factors in the intrinsic pathway showed that Melastoma leaf extract specifically targeted and caused a considerable deficiency in factor VIII (FVIII) levels (23 - 35 %) non-dose dependently. Results from the in vivo studies employing suitable animal models of thrombosis corroborated with the findings of in vitro clot-based assays and hence, confirmed the inherent anticoagulant properties of Melastoma leaf extract. The toxic and hemorrhagic propensity of this extract evaluated in an acute oral toxicity animal study underscored the absence of aberrant effects of the extract in vivo when administered at a high, single dose (5 g/ kg) for a short period of 14 days. However, subacute toxicity evaluations of the extract administered on a daily dose in regimen at various lower dosages (50, 75 and 100 mg/ kg) for 28 days. revealed an array of abnormal changes, notably hepatic venous dilatation and congestion. and hemorrhage in renal tissues. Nevertheless, cytotoxicity studies of the extract employing organ-specific cells and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) cell viability assay proved the absence of direct toxicity, as substantiated by preserved cellular integrity and high 50 % inhibitory concentration (ICSO) value of the extract (972 ± 2.57 ug/ml), in comparison to evident cytotoxic manifestations of heparin used as control reference. Collectively, the findings of this study suggested that the hot water extract of Melastoma leaves have high potential as an affordable alternative for future development of a potent and safe novel anticoagulant agent of natural origin.